Sunflower inbred lines screening for tolerance to white rot on stalk - Dedić Boško (Ratarstvo i Povrtarstvo, 2011)
Seventy sunflower (Helianthus annuus L) inbred lines were screened for tolerance to white rot on stalk. Plants were inoculated at the budding stage with 4-day old Sclerotinia mycelium grown on PDA medium. Mycelium was placed on the leaf top and covered with tin foil, and the leaf was put into transparent nylon bag in order to maintain high humidity. Spot length on leaf was measured and plant tolerance was determined at the full flowering stage. Obtained results were analyzed by analysis of variance. Tested lines showed significant variability in response to disease. Eleven lines had lesion length less than 50% compared to susceptible control, so they could be considered tolerant and potentially interesting for breeding program.